Investigation of water droplet size distribution in conventional and sustainable aviation turbine fuels - Ugbeh-Johnson, Judith; Carpenter, Mark; Okeke, Nonso Evaristus; Nnabuife, Somtochukwu Godfrey; Mai, Nathalie (Society of Automotive Engineers (SAE), 2022)
Water droplet size variation has been established in the literature as an important variable that influences the behavior and characteristics of water in fuel emulsion. However, with the growing demand for sustainable aviation fuels (SAF), no data is available that shows how these fuels will affect the size of dispersed water droplets and their frequency distribution. To address this lack of knowledge, this study explores and presents experimental results on the characterization of dispersed water droplets in alternative fuels and Jet A-1 fuel under dynamic conditions. The alternative fuels comprised of two fully synthetic fuels, two fuels synthesized from bio-derived materials, and one bio-derived fuel. The data and statistics presented reveal that water droplet frequency and size distribution are sensitive to changes in fuel composition. Observations showed an evident transition of the droplet percentile over time in the cumulative frequency distribution; this could be attributed to droplet coalescence to form larger droplets. Mean droplet diameters between 3 and 6 μm were observed for all the fuels tested. With further analysis based on recommendations proposed in this work, the data may assist in providing insight to filter manufacturers.
Keywords: Sustainable; Turbine fuels; Fuel systems; Aviation; Shedding; Jet fuel; Aircraft